1988
DOI: 10.1159/000288061
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Artificial Insemination with Donor Semen on the Psyche of the Husband

Abstract: It has been argued that artificial insemination with donor semen (AID) can be detrimental to the psyche of the sterile husband. This issue has been scrutinized on a larger scale empirical basis using four groups of husbands whose wives were either pregnant due to AID or were under AID without being pregnant yet or were pregnant without AID or were assumedly fertile without being pregnant. Psychometric data was obtained of the corresponding husbands. The results indicate that AID is no threat to the husbands of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
1

Year Published

1992
1992
2001
2001

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 3 publications
0
3
1
Order By: Relevance
“…The results of this study do not support those of Blaser et al (1988), who found that DI did not pose a threat to men, and that infertile men were not a psychological risk group. In contrast, this research suggests that men experience high levels of anxiety and distress about their infertility.…”
Section: Distress and Moodcontrasting
confidence: 99%
“…The results of this study do not support those of Blaser et al (1988), who found that DI did not pose a threat to men, and that infertile men were not a psychological risk group. In contrast, this research suggests that men experience high levels of anxiety and distress about their infertility.…”
Section: Distress and Moodcontrasting
confidence: 99%
“…In a study of 48 AID couples, Rosenkvist (1981) found that significantly more women than men believed that infertility was an emotional strain. Some men, however, became angry when their wives wanted to skip a month or stop AID (Bos et al, 1982). These studies indicate that infertility is a stressful experience that evokes emotional reactions, perhaps more so for women than men.…”
Section: Di$erences Between Wives and Husbands In Emotional Reactionsmentioning
confidence: 87%
“…Multiple specific stressors, which may differ for men and women, relate to each of these major factors. For example, one partner might resent or blame the other partner for the couple's infertility (Bos, van Dijk, & Lambers, 1982), both partners may be at different phases of the grieving process and be unable to support one another (D'Andrea, 1984), the expense of AID may pose a hardship, or a couple may experience a loss of privacy (Diamond, Christianson, Daniell, & Wentz, 1983) or a decline in sexuality (Bos et al, 1982;Diamond et al, 1983). Other stressors may include feeling unable to make plans (Frank, 1984), a sense of failure at each menstrual period (Blaser et al, 1988;Reading, Sledmere, & Cox, 1982), concerns about secrecy and confidentiality (Berger et al, 1986;Matot & Gustin, 1990), concern regarding legal rights to a child conceived by AID, or nonacceptance of the AID child by the nonbiologic father (Blaser et al, 1988;Dennerstein & Morse, 1988;Francis & Nosek, 1988;Matot & Gustin, 1990).…”
Section: Stress Of Infertility and Aidmentioning
confidence: 99%
See 1 more Smart Citation